Newly diagnosed diseases and the frequency of their occurrence in patients after a new coronavirus infection. Results of an International Register "Dynamics Analysis of Comorbidities in SARS-CoV-2 Survivors (ACTIV SARS-CoV-2)" (12-month follow-up) - G. P. Arutyunov; E. I. Tarlovskaya; A. G. Arutyunov; D. S. Polyakov; Yu. N. Belenkov; A. O. Konradi; Yu. M. Lopatin; A. P. Rebrov; S. N. Tereshchenko; A. I. Chesnikova; H. G. Hayrapetyan; A. P. Babin; et al. (Российский кардиологический журнал)
Aim. To analyze newly diagnosed diseases and features of the post-COVID course in patients after a coronavirus disease 2019 (COVID-19) within 12-month follow-up.Material and methods. A total of 9364 consecutively hospitalized patients were included in the ACTIV registry. Enrollment of patients began on June 29, 2020, and was completed on March 30, 2021, corresponding to the first and second waves of the pandemic. Demographic, clinical, and laboratory data, computed tomography (CT) results, information about inhospital clinical course and complications of COVID-19 during hospitalization were extracted from electronic health records using a standardized data collection form. The design included follow-up telephone interviews with a standard questionnaire at 3, 6, and 12 months to examine the course of post-COVID period.Results. According to the ACTIV registry, 18,1% of patients after COVID-19 had newly diagnosed diseases (NDDs) over the next 12 months. Hypertension (HTN), type 2 diabetes and coronary artery disease (CAD) prevailed in the NDD structure. Comparison of the age-standardized incidence of NDDs (HTN, CAD, diabetes) in the post-COVID period in the ACTIV registry with NDD incidence in 2019 according to Rosstat and the expected incidence of NDDs according to the EPOHA study revealed that HTN, diabetes, CAD in patients after COVID-19 were registered more often as follows: HTN by 7,0 and 4,4 times, diabetes by 7,3 and 8,8 times, CAD by 2,3 and 2,9 times, respectively. NDDs most often developed in patients aged 47 to 70 years. Comparison of the actual and expected number of cases of newly diagnosed HTN, CAD and diabetes depending on age showed that the actual number of cases in the population of patients in the ACTIV register is significantly higher than expected for patients aged 45-69 years and for patients with hypertension or diabetes and aged <45 years. Patients with NDDs, compared with patients without NDDs, had a more severe acute COVID-19 course. Statistically significant independent predictors of NDD occurrence (HTN and/or diabetes and/or CAD) within 1 year after hospital discharge were age (direct relationship), body mass index (direct relationship) and glucose levels upon admission to hospital (direct relationship).Conclusion. Available evidence suggests that a strategy for managing COVID-19 survivors should include mandatory screening for early detection of cardiovascular disease and diabetes, which will be key to reducing the risk of further COVID-19 consequences.